Mitos dan Konstruksi Kecantikan yang Dibangun dalam Iklan Jepang SK II “Bareskin Chat”: Analisis Kajian Semiotika Barthes & Wolf - Yuliani, Risa; Adji, M.; Saleha, Amaliatun (Universitas Diponegoro, 2022)
Women and beauty are something that is very attached for granted. Based on its history, beauty standards for women have been created for a long time. However, several beauty products have defined the existing beauty stereotypes, namely advertisements on SK II. This study shows how beauty construction works in women in SK II advertisements. This study applies the semiotic method using a qualitative approach. Therefore, the data collection technique in this study uses a literature study by applying a study of books, notes, literature, and various reports related to the issue to be solved. This study shows that women's beauty is represented far and even better in these advertisements than the myth of ideal beauty standards created by the mass media and the general public today. Women tend to lack self-confidence and the temptation to compare their appearance to others. <a href=